Contribution, Utilization, and Improvement of Legumes-Driven Biological Nitrogen Fixation in Agricultural Systems - Kebede, Erana (Frontiers in Sustainable Food Systems, 2021)
Legumes improve soil fertility through the symbiotic association with microorganisms, such as rhizobia, which fix the atmospheric nitrogen and make nitrogen available to the host and other crops by a process known as biological nitrogen fixation (BNF). Legumes included in the cropping system improve the fertility of the soil and the yield of crops. The advantages of legumes in the cropping system are explained in terms of direct nitrogen transfer, residual fixed nitrogen, nutrient availability and uptake, effect on soil properties, breaking of pests' cycles, and enhancement of other soil microbial activity. The best benefits from the legumes and BNF system can be utilized by integrating them into cropping systems. The most common practices to integrate legumes and their associated BNF into agricultural systems are crop rotation, simultaneous intercropping, improved fallows, green manuring, and alley cropping. However, the level of utilizing nitrogen fixation requires improvement of the systems, such as selecting appropriate legume genotypes, inoculation with effective rhizobia, and the use of appropriate agronomic practices and cropping systems. Therefore, using legumes at their maximum genetic potential, inoculation of legumes with compatible rhizobia, and using appropriate agronomic practices and cropping systems are very important for increasing food production. Importantly, the utilization of legumes as an integral component of agricultural practice in promoting agricultural productivity has gained more traction in meeting the demand of food production of the world populace. Priority should, thus, be given to value the process of BNF through more sustainable technologies and expansion of knowledge to the system.